Дослідження Северинівського городища на Поділлі - Болтрик, Ю.В.; Ігначек, М.; Оледзкі, Л. (Археологічні дослідження в Україні, 2010)
The paper is devoted to the recommencement after a 50-year break of archaeological works at Severynivka hillfort, a site of the Early Iron Age situated near Mezhyriv village of Zhmerynka Region in Vinnytsya Oblast.